ChemInform Abstract: A Catalyst‐Free Synthesis of Phosphinic Amides Using O‐Benzoylhydroxylamines. Issue 16 (March 2016) - Zhu, Rui; Pan, Chongqing; Gu, Zhenhua
Abstract: In contrast to conventional methods the novel protocol tolerates a broad range of secondary phosphine oxides and O‐benzoylhydroxylamines while providing the products in moderate to very high yields.